The 15 January 2022 Hunga Tonga Eruption History as Inferred From Ionospheric Observations. Issue 10 (24th May 2022) - Astafyeva, E.; Maletckii, B.; Mikesell, T. D.; Munaibari, E.; Ravanelli, M.; Coisson, P.; Manta, F.; Rolland, L.
Abstract: On 15 January 2022, the Hunga Tonga‐Hunga Ha'apai submarine volcano erupted violently and triggered a giant atmospheric shock wave and tsunami. The exact mechanism of this extraordinary eruptive event, its size and magnitude are not well understood yet. In this work, we analyze data from the nearest ground‐based receivers of Global Navigation Satellite System to explore the ionospheric total electron content (TEC) response to this event. We show that the ionospheric response consists of a giant TEC increase followed by a strong long‐lasting depletion. We observe that the explosive event of 15 January 2022 began at 04:05:54UT and consisted of at least five explosions. Based on the ionospheric TEC data, we estimate the energy released during the main major explosion to be between 9 and 37 Megatons in trinitrotoluene equivalent. This is the first detailed analysis of the eruption sequence scenario and the timeline from ionospheric TEC observations. Plain Language Summary: On 15 January 2022, the giant explosion of the Hunga Tonga‐Hunga Ha'apai volcano shook the atmosphere of the Earth and generated a tsunami. The exact mechanism and timing of the eruption are not well understood yet, nor is the series of events that occurred directly following the first event. Many scientists are trying to understand the chronology of the eruption using different types of data. Here we investigate the signature of the eruption as recorded in Earth's ionosphere, the electrically conductive layer of the atmosphere from about 85 to 800 km of altitude. We observe variations in the total electron content (TEC) of the ionosphere using Global Navigation Satellite System receivers (commonly known as GPS receivers). Variations in the TEC through time and space are caused by sound waves from the eruption traveling through the ionosphere. We use these variations to constrain the timing of the eruptive events, identifying at least five major explosions during this eruption. In addition, we use the amplitude of TEC variations to estimate that the largest explosion released energy of about 9–37 Megaton in trinitrotoluene equivalent. This is the first detailed analysis of the eruption scenario and the timeline from ionospheric TEC observations. Key Points: Ionospheric total electron content (TEC) data reveal that the 15 January 2022 Hunga Tonga volcanic eruption involved at least five large explosions between 4 and 5UT From TEC observations, we estimate the onset time to be 04:05:54UT and the main explosion energy release of 9–37 Megatons trinitrotoluene equivalent The eruption‐driven shock wave caused an unprecedentedly strong and long‐lasting depletion in the ionosphere